Product placement na tle innych przekazów handlowych. Prawna regulacja w ustawie o radiofonii i telewizji - Bagieńska-Masiota, Aleksandra (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
In 2011, the Polish legislature amended Broadcasting Law to match the laws of the European Union, introducing the definition of product placement, explained in the law as the placement of a product, conducted for a fee and admissible under legally stipulated circumstances, and the placement of a topic as an inadmissible form of promotional activities. In the author’s opinion, the legal provisions pertaining to product placement stipulated in the Broadcasting Law of 2011 are worthy of approval. They clarified a legal ambiguity in terms of the legal qualifications and restrictions on product placement on radio and TV. The said regulations do not pertain to the printed press, computer games and other non-periodical print publications, however
Product placement’ versus other commercial messages. Legal provisions in Broadcasting Law